Rethinking Teaching Team-Based Learning: The Challenges and Strategies for Medical Education in a Pandemic - Yun Li; Nicholas A. Sears; Ian V. J. Murray; Kamlesh K. Yadav (SAGE Publishing, 2021)
The medical education system in the United States has gone through a rapid transition to emergency remote teaching as a consequence of the COVID 19 pandemic. For the Engineering Medicine (EnMed) track of the College of Medicine at Texas A&M University, the most challenging aspects are the transition from in-class team-based learning (TBL) to online sessions and virtual facilitation with an interdisciplinary group of faculties. This article outlines the TBL format used in the EnMed curriculum, along with challenges in delivery, student perspective, and strategies for transitioning existing TBL online.